2012
DOI: 10.1515/cclm-2011-0856
|View full text |Cite
|
Sign up to set email alerts
|

Plasma total homocysteine is a determinant of carotid intima-media thickness and circulating endothelial progenitor cells in patients with newly diagnosed hypertension

Abstract: Our results suggest that Hcy might increase carotid artery IMT by reducing EPCs numbers. Possible involvement of Hcy in the reduction of EPCs number in hypertensive patients might be in part mediated by Hcy influence on the TAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Homocysteine (Hcy), another emergent CV risk factor [ 94 ], was shown to decrease EPC count and to impair EPCs activity [ 95 ]. Interestingly, in patients with newly diagnosed hypertension, Bogdanski et al found that Hcy levels are significantly associated with increased carotid IMT and decreased number of CFU-ECs and proposed as explanation that Hcy may interfere with the redox setting [ 96 ]. Vitamin D deficiency has been associated with CVD [ 97 , 98 ]; more recently, vitamin D has been suggested to exert effects on the CV system [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Homocysteine (Hcy), another emergent CV risk factor [ 94 ], was shown to decrease EPC count and to impair EPCs activity [ 95 ]. Interestingly, in patients with newly diagnosed hypertension, Bogdanski et al found that Hcy levels are significantly associated with increased carotid IMT and decreased number of CFU-ECs and proposed as explanation that Hcy may interfere with the redox setting [ 96 ]. Vitamin D deficiency has been associated with CVD [ 97 , 98 ]; more recently, vitamin D has been suggested to exert effects on the CV system [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…During HHcy, increased reactive oxygen species, matrix metalloproteinase, and decreased endothelial nitric oxide cause vascular constriction and stiffness, which could lead to essential hypertension [27] . A clinical study came to the same conclusion, that Hcy was a determinant of vascular thickness and compliance in hypertensive patients [28] , [29] and that HHcy increased the risk of cerebrovascular complications and glomerular sclerosis [30] , [31] . There is a pathogenic effect of Hcy on the vasculature, but the data on the relationship between Hcy levels and vascular biology at the initial stages of hypertension was limited.…”
Section: Discussionmentioning
confidence: 96%
“…The Framingham study (9) reported that the number of EC colony‐forming units (referred to as EPCs) in peripheral blood (PB) was associated with cardiovascular risk scores, a clinical index for 10‐year risk of developing coronary heart disease (CHD) based on age, total cholesterol level, HDL cholesterol level, smoke, and systolic blood pressure. Decreased EPC population is associated with carotid intima‐media thickness and flow‐mediated vascular dilation in patients with hypertension (13, 14) and is also associated with endothelial dysfunction in patients on dialysis with chronic kidney disease (11, 15). It was reported that elevated plasma levels of homocysteine (Hcy) are associated with reduced circulating EPC counts in patients with CHD (16).…”
mentioning
confidence: 99%